Knowledge mapping analysis of mental health research on COVID-19 - Zhou, Runjin; Lin, Xiaoling; Xu, Jiamei; Lin, Xingdong; Wu, Zhibing (Frontiers in Psychiatry, 2022)
Objective. To explore the development context, research hotspots, and frontiers of mental health on COVID-19 by bibliometric analysis. Methods. Publications about mental health research from 2019 to 2021 were retrieved from the Web of Science Core Collection (WoSCC). VOSviewer 1.6.17 was used to analyze the co-authorship of countries, institutes, and authors. Co-citation of cited authors/references were also analyzed by VOSviewer. CiteSpace V.5.8.R3 was used to analyze keywords cluster and forecast research frontiers. Results. A total of 8,856 literatures were retrieved, including 1,0559 research institutes and 1,407 academic journals. The most published country and institutes were the United States (2190) and University of London (373). Wang, Chengyu owned the highest co-citations (1810). Trending keywords may indicate frontier topics, including “anxiety”, “depression”, “psychological distress”, “quarantine”, “post-traumatic stress disorder (PTSD)”, “insomnia”, “Healthcare workers”. Conclusions. The most common psychological problems of people during the epidemic are anxiety and depression. Insomnia and PTSD need to be solved under the normalization of the epidemic. GAD-7 and PHQ-9 scales are the most convenient and effective for screening anxiety and depression. Healthcare workers, older adults, and college students should be concerned, social and family support is essential.